Effect of ripening and coating on characteristics of Dangke cheese inoculated with a starter culture of Lactococcus lactis subsp. lactis FNCC-0086 - Malaka Ratmawati; Amrawaty A. Amidah; Putranto Wendry Satriadi; Kadir Rizky Widiyanty; Arief Fitri Armianty (BIO Web of Conferences)
Dangke is a traditional dairy product from Enrekang Regency, South Sulawesi, Indonesia, categorized as cheese based on its shape and manufacturing process. This traditional cheese has a very short shelf life, lasting only about 2 days at room temperature and approximately 5 days when refrigerated. Innovative product development to create cultured cheese varieties as a diversification of dangke cheese with a longer shelf life is carried out by inoculating a starter culture of lactic acid bacteria, Lactococcus lactis subsp. lactis FNCC-0086. In this study, Dangke cheese is made from fresh cow's milk curdled with papaya latex. In other conditions, Dangke Cheese can also be made from buffalo milk, goat milk, or even horse milk. The papaya latex is diluted with distilled water in a 1:10 ratio. The milk is pasteurized at 85°C for 1 minute, after which 0.03% of papaya latex is added and stirred slowly until curd forms. The starter culture is inoculated once the milk reaches a temperature of 30°C. The curd is then molded using a semicircular mold with a diameter of 10 cm, resembling the original dangke mold. It is compacted by pressing the curd with a spoon to make the cheese more compact, until no more whey liquid comes out of the curd. The molded cheese is then placed on a cheese rack and ripened at temperatures of 5°, 15°, and 25°C for 3, 6, 9, and 12 days before being coated with beeswax. Dangke cheese was evaluated for its physical-chemical properties. The optimal result was Dangke cheese stored at 5°C for 12 days, exhibiting a pH of 4.36, 0.53% lactic acid, 21.53% protein, 48.98% water, 13.05% fat, 13.52% lactose, and 2.92% minerals after being coated with beeswax.